Livros à mão cheia: o livro como veículo de produção acadêmica - MENANDRO, Paulo Rogério Meira (2013)
This essay discusses the importance of books as means of scientific publishing. Arguments are presented which favors the view that periodicals and books, in several areas of knowledge, constitute different modes for dissemination of academic findings, complementary in the fulfillment of relevant functions for the development of sciences and for both professional formation and development. The methodology adopted in recent years in Brazil for evaluation of books produced within Graduate programs in Psychology is described and commented.